The first record of Hallucigenia-like lobopodians from the lower Jince Formation (Cambrian, Miaolingian) of the Příbram–Jince Basin - Vojtěch Kovář; Oldřich Fatka (Swiss Journal of Palaeontology)
Abstract A fossil interpreted as a long-legged lobopodian animal (Hallucigenia? sp.) is described from the middle Cambrian (Miaolingian) Jince Formation of the Příbram–Jince Basin (Barrandian area, Czech Republic). The fossil shows a long vermiform trunk, at least twenty-five long thin lobe-like appendages indicating the ventral side, and the bases of at least 12 thin spines protruding dorsally. Palynological processing of fine-grained rock samples from ca. 100 m higher in the section yielded several tens of small carbonaceous fossils attributable to armoured lobopodians alongside wiwaxiid sclerites and additional abundant organic-walled microfossils. The Bohemian specimen and recent finds of rare lobopodians in Australia, China, and the USA, together with many occurrences of isolated spines interpreted as belonging to hallucigeniids, demonstrate that lobopodians were much more geographically widespread than previously thought. The Bohemian macrofossil is the youngest known occurrence of a hallucigeniid; this specimen and the microfossil material extend the stratigraphic range of the group within the traditional early to middle Cambrian interval.